Effects of competitor density and rainfall regime on the long-term population dynamics of an herbivore community in a western African savannah - (:unkn) unknown (My University, 2018)
Despite many scientific articles were devoted to study aspects of community ecology of ungulates in African savannahs, only very few studies focused on communities from Western Africa. In this paper, we analyse the interspecific interactions of savannah ungulates in the Nazinga Game Ranch (Burkina Faso) in relation to rainfall patterns and potential competitor density, using long-term (1985-2008) line-transect data. We estimated the population sizes of all species by using distance sampling. There was no effect of the year on the population sizes of all the species, but, when 5-year-period groups were analyzed, there were significant fluctuations over time intervals for at least some of the species. Generalized Linear Models on the interspecific relationships (either positive or negative) between pairs of species would suggest that interannual population size fluctuations of the various ungulates were likely attributable to fluctuations in poaching intensity, the influences of rainfall regimes (for at least three browser species), and negative density dependence.
Keywords: African Research